2016
DOI: 10.1515/jpem-2016-0109
|View full text |Cite
|
Sign up to set email alerts
|

A germline mutation of HRPT2/CDC73 (70 G>T) in an adolescent female with parathyroid carcinoma: first case report and a review of the literature

Abstract: Parathyroid carcinoma is a rare cause of primary hyperparathyroidism amongst children, with only nine previously reported cases. The objective of the study was to present the first pediatric case with a germline CDC73 (formerly known as HRPT2) mutation, and to review the literature. A 14-year-old girl presented with pathologic slipped capital femoral epiphysis (SCFE). The patient was noted to have an elevated calcium level of 3.4 mmol/L (13.4 mg/dL), a parathyroid hormone (PTH) level of 1013 ng/L (1013 pg/mL),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…The CDC73 gene mutation is related to sporadic parathyroid carcinoma and HPT‐JT syndrome with a relatively high rate of parathyroid carcinoma, which is one of the main reasons for persistent or recurrent PHPT and may lead to life‐threatening hypercalcaemia . Previous studies of CDC73 gene screening in children have been limited to case reports; therefore, the present study is the largest study incorporating CDC73 gene analysis that focused solely on paediatric PHPT. A high CDC73 gene mutation rate of 25% (6/24) combined with high rates of recurrence (3/6) and the tendency to be malignant (two cases of atypical adenoma and one case of carcinoma) was found in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The CDC73 gene mutation is related to sporadic parathyroid carcinoma and HPT‐JT syndrome with a relatively high rate of parathyroid carcinoma, which is one of the main reasons for persistent or recurrent PHPT and may lead to life‐threatening hypercalcaemia . Previous studies of CDC73 gene screening in children have been limited to case reports; therefore, the present study is the largest study incorporating CDC73 gene analysis that focused solely on paediatric PHPT. A high CDC73 gene mutation rate of 25% (6/24) combined with high rates of recurrence (3/6) and the tendency to be malignant (two cases of atypical adenoma and one case of carcinoma) was found in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of PHPT is estimated to be approximately 2-5 cases per 100,000 cases in the childhood population . Parathyroid carcinoma is a rare cause of PHPT and is associated with 0.5 to 5% of all cases of PHPT (Wynne et al 1992) with only nine reported cases in childhood (Serrano- Gonzalez et al 2016). Thakker reviews the most current understanding of the molecular etiology of parathyroid tumors (Thakker 2016).…”
Section: Parathyroid Adenoma/carcinomamentioning
confidence: 99%
“…Individuals with HPT-JT syndrome develop parathyroid adenomas and carcinoma due to a mutation in CDC73, but they may or may not develop additional associated tumors. In one of the few reported cases of pediatric parathyroid carcinoma in a 14 year old female, a CDC73 germline mutation was identified (Serrano- Gonzalez et al 2016). Those with HPT-JT frequently have a single adenoma or carcinoma whereas those with MEN1 usually have multi-glandular parathyroid disease.…”
Section: Parathyroid Adenoma/carcinomamentioning
confidence: 99%
“…The PHPT is cancerous in 20 %. Parathyroid cancer has been reported as early as age 8 years [91,92]. Rarely, a parathyroid neoplasm in a normocalcemic carrier may be initially recognized only with ultrasound [93].…”
Section: Pathology Of the Parathyroids In Hpt-jtmentioning
confidence: 99%